Transformational Leadership Without Equality Is Neither: Challenging the Same Old System - Levac, Leah (Atlantis)

(untitled) (Mount Saint Vincent University, 2008)
This paper reports on my experience in the 2004/2005 University of New Brunswick sponsored 21 Leaders initiative, on the presentation of the initiative by me and a colleague at an international conference - Women as Global Leaders - and on the capacity of 21 Leaders to contribute to transformation in New Brunswick.